Sosialisasi Laporan Keuangan PMI Kabupaten Blitar: Transparan, Akuntabel dan Kepercayaan Publik - Kornitasari, Yenny (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2023)
The Indonesian Red Cross (PMI) of Blitar District is a public sector organization responsible for managing social funds from various sources. However, its financial reporting does not meet Indonesian accounting standards, indicating a lack of accountability. This is due to the absence of specialized personnel in financial management. This community service activity aims to enhance transparency, accountability, and understanding of financial reports. It emphasizes the importance of transparency and accountability and provides hands-on practice in compiling financial reports and infographics, specifically for PMI Blitar District. By using Canva, the organization can enhance financial data visualization and presentation, making it easier for the public to understand. The results from this community service indicate that training using Canva can improve the quality of financial reports and strengthen public trust. Furthermore, collaboration in report creation and flexibility in presentation formats add value to the use of Canva.Palang Merah Indonesia (PMI) Kabupaten Blitar merupakan organisasi sektor publik yang bertanggung jawab mengelola dana sosial dari berbagai sumber. Namun, pelaporan keuangannya belum memenuhi standar akuntansi Indonesia, menunjukkan kurangnya akuntabilitas. Hal ini disebabkan oleh tidak ada tenaga khusus dalam manajemen keuangan. Kegiatan pengabdian ini bertujuan meningkatkan transparansi, akuntabilitas, dan pemahaman terhadap laporan keuangan. Membahas pentingnya transparansi dan akuntabilitas serta memberikan praktik langsung dalam penyusunan laporan dan infografis keuangan, khususnya bagi PMI Kabupaten Blitar. Dengan menggunakan Canva, organisasi dapat meningkatkan visualisasi dan penyajian data keuangan, sehingga mempermudah pemahaman oleh publik. Hasil dari kegiatan pengabdian ini menunjukkan bahwa pelatihan menggunakan Canva dapat meningkatkan kualitas laporan keuangan dan memperkuat kepercayaan publik. Selain itu, kolaborasi dalam pembuatan laporan serta fleksibilitas dalam format penyajian menjadi nilai tambah dalam penggunaan Canva.